3D and 4D Printing of Polymers for Tissue Engineering Applications - Tamay, Dilara Goksu; Dursun Usal, Tugba; Alagoz, Ayse Selcen; Yucel, Deniz; Hasirci, Nesrin; Hasirci, Vasif (Frontiers in Bioengineering and Biotechnology, 2019)
3D and 4D printing emerge as next generation fabrication techniques spanning various research areas such as engineering, chemistry, biology, computer science, and materials science. 3D printing enables the fabrication of complex forms with high precision through layer-by-layer addition of different materials. Use of intelligent materials which change shape or color, produce electrical current, become bioactive, or perform an intended function in response to an external stimulus, paves the way for the production of dynamic 3D structures, which is now called 4D printing. 3D and 4D printing techniques have high potential in the production of scaffolds to be applied in tissue engineering, especially in constructing patient specific scaffolds. Furthermore, physical and chemical guidance cues could be printed with these methods to improve the extent and rate of targeted tissue regeneration. This review presents a comprehensive survey of 3D and 4D printing methods, and the advantage of their use in tissue regeneration over other scaffold production approaches.